Influence of acclimatization on serum enzyme changes in soldiers during exertional heat stress - Radaković Sonja; Marić Jelena; Šurbatović Maja; Vasiljević Nađa; Milivojević Mladen (Vojnosanitetski Pregled)
Background/Aim. Exertional heat stress is common problem in military services. The aim was to examine changes in serum concentrations of some enzymes in soldiers during exertional heat stress test (EHST) as well as the effects of 10-days passive or active acclimatization in climatic chamber. Methods. Forty male soldiers with high aerobic capacity, performed EHST either in cool (20 ºC, 16 ºC Wet bulb globe temperature - WBGT), or hot (40 ºC, 25 ºC WBGT) environment, unacclimatized, or after 10 days of passive or active acclimation. Physiological strain was measured by tympanic temperatures (Tty) and heart rates (HR). Concentrations of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and creatine-kinase (CK) were measured in blood samples collected before and immediately after EHST. Results. Exertional heat stress test in hot conditions induced physiological heat stress (increase in Tty and HR), with significant increase in concentrations of all enzymes in unacclimatized group: ALT (42.5 ± 4.2 before vs 48.1 ± 3.75 U/L after EHST, p < 0.01), AST (24.9 ± 5.1 vs 33.4 ± 4.48 U/L, p < 0.01), LDH (160.6 ± 20.2 vs 195.7 ± 22.6 U/L, p < 0.001) and CK (215.5 ± 91.2 vs 279.1 ± 117.5 U/L, p < 0.05). In acclimatized soldiers there were no significant changes in concentrations of ALT and AST, while concentration of CK was significantly higher. Concentrations of LDH were significantly higher in all investigated groups, regardless of temperature conditions. Conclusion. In trained soldiers, 10-days passive or active acclimatization in climatic chamber can prevent increase in serum concentrations of ALT and AST, induced by exertional heat stress. Increase of serum concentrations of CK and LDH was induced by physical strain itself, with no additional effect of heat stress.